2010
DOI: 10.3810/pgm.2010.09.2197
|View full text |Cite
|
Sign up to set email alerts
|

Migraine, Tension-Type Headache, and Attention-Deficit/Hyperactivity Disorder in Childhood: A Population-Based Study

Abstract: Migraine and TTH are not comorbid to ADHD overall, but are comorbid to hyperactive-impulsive behavior. Providers and educators should be aware of the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
56
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 44 publications
6
56
1
Order By: Relevance
“…Primary headache, such as migraine and tension-type headache, affects Brazilian children with a prevalence rate of 12.3% and 4.2%, respectively (2). Although the origin or worsening of headache in children and adolescents may also be related to temporomandibular joint disorder (TMJD), few studies have addressed this association.…”
Section: Introductionmentioning
confidence: 99%
“…Primary headache, such as migraine and tension-type headache, affects Brazilian children with a prevalence rate of 12.3% and 4.2%, respectively (2). Although the origin or worsening of headache in children and adolescents may also be related to temporomandibular joint disorder (TMJD), few studies have addressed this association.…”
Section: Introductionmentioning
confidence: 99%
“…Strine et al [23] evidenced an odds ratio of 2.6 to have inattention and hyperactivity in children who referred headache, and Genizi et al showed that learning disabilities and ADHD are more common in children and adolescents who are referred for neurological assessment for primary headaches than those described in the general pediatric population [1], while Arruda et al demonstrated that migraine and TTH are not comorbid to ADHD overall but are comorbid to hyperactive-impulsive behavior [20].…”
Section: Introductionmentioning
confidence: 97%
“…Concentration difficulties and hyperactivity are psychological predictors of headaches [18], and at the same time, frequent headaches may increase distractibility and are associated with impaired attention span [19] and hyperactivityimpulsivity disease [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, from the last 2 decades, much attention has been given to the relevance of psychiatric comorbidities, and neurological and psychological problems 3946. The pathophysiology of migraine implicates vascular and neurological mechanisms.…”
Section: Introductionmentioning
confidence: 99%